Research trends and hotspots of acupuncture therapy for obesity from 2004 to 2023: A bibliometric analysis - Jinkun Wang; Kangdi Cao; Zhaoyi Chen; Tianli Lyu; Qiuyu Xia; Lu Liu; Bin Li (Complementary Therapies in Medicine)
Background: Acupuncture has been increasingly used in obese people, yet no bibliometric analysis of acupuncture studies for obesity exists. This bibliometric study analyzed research trends, cooperation, and knowledge dissemination on acupuncture for obesity over the past 20 years to inform future directions. Objectives: To investigate the characteristics, hotspots, and frontiers of global scientific output in acupuncture research for obesity over the past two decades. Methods: We retrieved publications on acupuncture for obesity published from 2004 to 2023 from the Web of Science Core Collection. Using Citespace, VOSviewer, and Bibliometrix, we analyzed and visualized the publications, countries, institutions, authors, journals, and keywords from various angles. Results: A total of 357 articles were retrieved. The results showed that the number of annual publications on acupuncture for obesity has increased over time. China had the most publications (217 articles, 60.87 %), with Chengdu University of Traditional Chinese Medicine (24 articles, 6.72 %) as the most prolific institution. Ergene Neyhan, Huang Wei, and Zhou Zhongyu were the most productive authors (9 articles), and the article published by Cho SH in 2009 was the most cited article (60 citations). The most published journal was Evidence-based Complementary and Alternative Medicine, while the Journal of American Journal of Chinese Medicine was the most frequently cited. Recently, “electroacupuncture” “insulin resistance” and “systematic review” appeared frequently. The research hotspots and trends of acupuncture for obesity mainly focus on interventions, hotspot diseases, and mechanism exploration. According to keyword analysis, randomized controlled trials of catgut embedding and mechanistic studies of gut flora are the trends for future research. Conclusion: Although China is the leading producer, multinational co-operation still needs to be strengthened. Currently, the main interventions for obesity were acupuncture and electroacupuncture, and the hot diseases were obesity combined with polycystic ovary syndrome and metabolic syndrome. In addition, randomised controlled trials of catgut embedding and mechanistic studies of gut flora may be potential directions for future research in the field of acupuncture for obesity.